2020
DOI: 10.17221/144/2020-pse
|View full text |Cite
|
Sign up to set email alerts
|

Soil quality with traditional management in the Chambira native community

Abstract: The traditional management applied by the Native Community of Chambira (NCCh) is based on agroforestry plots with diverse species and areas with rotation of legumes, cassava and maize. The objective was to evaluate behaviour of the physicochemical indicators of soil quality with traditional crop management in the NCCh. A completely randomised design was applied, where the treatments were traditional mixed fruit management (MF), crop rotation (CR) and native forest (NF) as reference. Physical indicators of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
(16 reference statements)
0
1
0
Order By: Relevance
“…(b) Negative impact on pH (P < 0.01), the R 2 shows that age contributes 80.07% of the pH variation (Table 5). This behaviour expresses an acidification process, although the pH remains at a neutral level, a typical condition for this type of soil (Uribe et al 2002;Olivares et al 2022a;Serrao et al 2022), however, the reduction of pH is associated with the loss of Ca and Mg (Bohn et al 1993;Rajkishore et al 2017;Florida & Acuña 2020), which can be observed in the results (Table 2) and is possibly responsible for the reduction in crop yield. (c) Negative impact (P < 0.01) on P levels, the R 2 evidence that age contributes 79.20% to P variation (Table 6).…”
Section: Correlation Analysis and Modellingmentioning
confidence: 86%
“…(b) Negative impact on pH (P < 0.01), the R 2 shows that age contributes 80.07% of the pH variation (Table 5). This behaviour expresses an acidification process, although the pH remains at a neutral level, a typical condition for this type of soil (Uribe et al 2002;Olivares et al 2022a;Serrao et al 2022), however, the reduction of pH is associated with the loss of Ca and Mg (Bohn et al 1993;Rajkishore et al 2017;Florida & Acuña 2020), which can be observed in the results (Table 2) and is possibly responsible for the reduction in crop yield. (c) Negative impact (P < 0.01) on P levels, the R 2 evidence that age contributes 79.20% to P variation (Table 6).…”
Section: Correlation Analysis and Modellingmentioning
confidence: 86%